Approaches to Corporate Debt Restructuring in the Wake of Financial Crises - Laryea, Thomas (IMF Staff Position Notes; Staff Position Note, 2010)
This paper starts from a discussion of the economic case for moderated government intervention in debt restructuring in the nonfinancial corporate sector. It then draws on lessons from past crises to explain three broad approaches that have been applied to corporate debt restructurings in the aftermath of a crisis. From there, it addresses challenges in designing and implementing a comprehensive debt restructuring strategy and draws together some key principles.